Strategy For Developing the Quality of Public Services in The Sector at The Baruga Village Office, Baruga District Kendari City - Daming, Burhanudin; Nur, Muh.; Supriaddin, Nofal (International Journal of Management and Education in Human Development, 2024)
This study aims to find out and analyze (1) the quality of public services in the Baruga Village Office, Baruga District, Kendari City; and (2) Strategyes in improving the quality of public services at the Baruga Village Office, Baruga District, Kendari City. The respondents in this study were 35 people. The analysis tools used are quantitative descriptive research, namely using Internal Factor Evaluation (IFE) and External Factor Evaluation (EFE). Based on the results of the study, it can be concluded that (1) The quality of public services at the Baruga Village Office, Baruga District, Kendari City as the center of public services at the village level, carries out its main duties and functions to provide public administration services to the community. The implementation of public services provided in general, the quality of service has been optimally reviewed from five dimensions, namely tangible, reliability, responsiveness, assurance, emphaty; and (2) The strategy in improving the quality of public services at the Baruga Village Office, Baruga District, Kendari City is in quadrant 1, namely supporting aggressive Strategyes. The strategy that can be applied in quadrant 1 is to support aggressive growth policies (growth-oriented strategy) so that it can use the SO (strength and opportunity) strategy. The SO strategy pursued by the Baruga Village Office, Baruga District, Kendari City is to hold training specifically for employees in order to improve the quality of human resources, establish new policies that support the development of community empowerment programs and improve the quality of services by improving and developing human resources to increase public trust.